2015
DOI: 10.1302/0301-620x.97b9.34532
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcaemia following the use of antibiotic-eluting absorbable calcium sulphate beads in revision arthroplasty for infection

Abstract: Periprosthetic joint infection (PJI) is a devastating complication for patients and results in greatly increased costs of care for both healthcare providers and patients. More than 15 500 revision hip and knee procedures were recorded in England, Wales and Northern Ireland in 2013, with infection accounting for 13% of revision hip and 23% of revision knee procedures. We report our experience of using antibiotic eluting absorbable calcium sulphate beads in 15 patients (eight men and seven women with a mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 22 publications
3
89
0
Order By: Relevance
“…Kallala et al describes a case report of 15 patients whom received absorbable calcium beads following infected prosthetic joint revision surgery of the hip and knee. They found that 3 patients developed hypercalcaemia with 1 patient requiring treatment in the form of intravenous rehydration and bisphosphonates [10]. The paper concluded that they recommend routine serum calcium measurements postoperatively in patients who have had absorbable calcium beads inserted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kallala et al describes a case report of 15 patients whom received absorbable calcium beads following infected prosthetic joint revision surgery of the hip and knee. They found that 3 patients developed hypercalcaemia with 1 patient requiring treatment in the form of intravenous rehydration and bisphosphonates [10]. The paper concluded that they recommend routine serum calcium measurements postoperatively in patients who have had absorbable calcium beads inserted.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the case report is to highlight the risk of hypercalcaemia from the use of antibiotic loaded calcium sulphate beads and ensure doctors take suitable precautions to either prevent this from happening, or diagnose and treat promptly. A review of the surrounding literature shows that this complication has been previously reported [10]; however, no cases published thus far have required surgical intervention to normalise calcium levels.…”
Section: Introductionmentioning
confidence: 95%
“…In one revision TKA, there was a case of persistent wound drainage that resolved without surgical intervention. Additionally, Kallala and Haddad studied 15 hip and knee revision patients that were implanted with CSBs in an observational case series [26]. They found that one patient had clinical signs of infection with raised inflammatory markers at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin and tobramycin were used in calcium sulfate beads at each surgery and results demonstrated an overall 2.4% failure due to recurrent infection or new infection. Finally, a cohort of 15 patients treated with single-stage revision and calcium sulfate beads reported a 20% rate of hypercalcemia, with one of three patients with hypercalcemia requiring treatment for this complication [59]. Commercially prepared calcium sulfate with tobramycin (OSTEOSET, Wright Medical) has been approved for use in other countries; however, antibiotic-laden calcium sulfate is not yet approved for use in the USA.…”
Section: Novel Treatment Modalitiesmentioning
confidence: 99%